Otimização do custo, impacto ambiental e conforto de passarelas de estrutura mista aço-concreto - Tres Junior, Fernando Luiz (2023)
Optimization techniques can be of great help in structural design, obtaining optimal solutions through a rational search method. In addition to reducing project costs, other objectives can be considered, such as environmental impacts and user comfort. In this sense, this work proposes the multi-objective optimization of footbridges with a steel-concrete composite structure through the development and application of a computer program. The objectives of the optimization problem are to minimize monetary costs, carbon dioxide emissions and vertical accelerations generated by vibrations in the structure. For this purpose, the Harmonic Search method is implemented, a metaheuristic technique that is analogous to jazz musical improvisation. The geometry of the footbridge consists of two steel beams, mechanically connected to a solid reinforced concrete slab by head-type pins, considering different spans to be overcome. To ensure that the solutions are feasible, restrictions are used that follow the guidelines of current Brazilian regulations. The variables are the concrete strength of the slab, the slab thickness, the cross-sectional dimensions of the welded steel I-beam and the degree of interaction of the composite beam. The results show an explicit direct linear correlation between the cost and the emission of the structure, indicating that solutions with good economic performance are also efficient in terms of CO2 emissions. For every R$7.70 reduced in cost, 1 kg of CO2 emissions per meter of the walkway are avoided. In order to improve pedestrian comfort levels from minimum to medium, a considerable increase in the cost and emissions of the structure is required, depending on its span, reaching 89% for a 25-meter span. On the other hand, increasing the comfort level from medium to maximum implies increases of only 8.57%. While the beam is responsible for approximately 90% of the cost of the structure, CO2 emissions from the slab correspond to 20% to 40% of the total emissions of the structure. The optimal ratios between the span and the height of the beam web were 20.47 for minimum comfort, 17.29 for medium comfort and 17.09 for maximum comfort. Finally, the analysis of alternative scenarios shows that using damping devices can be an efficient solution to reduce accelerations and increase pedestrian comfort.